Bezrobocie osób niepełnosprawnych w Polsce w latach 1999-2006 - Politaj, Adriana (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
This article presents the scale of unemployment of handicapped persons in Poland between 1999 and 2006. This presentation characterizes unemployment across different population groups of disabled persons. The analysis was based on labour market data and survey of economic activity. This article highlights the directions of changes on labour market in relation to the situation of disabled persons. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 278-288